Analysis in Decision Making for XAUUSD (Gold/USD) Pair Transactions in Futures Trading - Johannes Taruli Pakpaharan (CV. Publikasi Indonesia, 2024)
Nowadays, many trading instruments, such as XAU/USD commodity futures trading, a label for spot gold traded in the foreign exchange market, are offered. Gold (XAU) is traded against the US dollar (USD), and its price represents the cost of one ounce of gold in USD. XAU/USD is traded like any other traditional currency in the forex market. This study explores how fundamental and technical analysis can be used as a basis for better decision-making in gold futures trading. The research method used is qualitative, with a descriptive analysis approach based on secondary data in the market. So, in the summary of the analysis results, it is found that fundamental and technical analysis is a tool used for decision-making in gold transactions and futures trading. Decision-making in gold transactions in futures trading should be based on fundamental and technical analysis at a minimum. Decision-making based solely on the results of one analysis alone can be fatal. Various sources of fundamental and technical analysis tools can be used as a decision-making tool in gold and futures trading.